2003
DOI: 10.1093/ndt/gfg403
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density, biochemical markers and skeletal fractures in haemodialysis patients

Abstract: In conclusion, the Z-score at the mid-radius was decreased in HD patients and correlated with high serum PTH but not with fractures. Bone fractures were associated with the time passed on HD and with a low total body Z-score. Rib fractures were frequent and associated with a poor nutritional state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
9
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(130 citation statements)
references
References 22 publications
10
106
9
5
Order By: Relevance
“…Specifically, bone with low turnover is associated with microstructural abnormalities, whereas bone with high turnover is associated with material and mechanical property abnormalities. Reduced bone quality of patients with either low-or high-turnover ROD may contribute to the known decreased mechanical competence in these patients [8][9][10][11][12][13][14] but for two different turnover-dependent reasons. These findings call for additional studies to evaluate modified treatment regimens for ROD by using tailored therapies for patients with low-or high-turnover bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, bone with low turnover is associated with microstructural abnormalities, whereas bone with high turnover is associated with material and mechanical property abnormalities. Reduced bone quality of patients with either low-or high-turnover ROD may contribute to the known decreased mechanical competence in these patients [8][9][10][11][12][13][14] but for two different turnover-dependent reasons. These findings call for additional studies to evaluate modified treatment regimens for ROD by using tailored therapies for patients with low-or high-turnover bone.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The potential link between bone turnover and bone quality is an important question meriting study because of the relatively high incidence of fractures reported to occur with abnormal turnover. [8][9][10][11][12][13][14] Thus, the specific aim of this study was to advance the understanding of this potential link by quantifying how the microstructural parameters, material composition, and nanomechanical properties vary in bone with low-or high-turnover renal osteodystrophy (ROD) compared with bone with normal turnover from normal volunteers. …”
mentioning
confidence: 99%
“…Moreover, CKD patients show different patterns of bone loss. Whereas some patients have a minimal bone loss, others show rapid bone losses 86. Additionally, the presence of aorta calcification and spinal osteoarthritis may bias BMD measurement,88 being the hip and the radius better sites for the BMD assessment.…”
Section: Bone and Musculoskeletal Abnormalities In Chronic Kidney Dismentioning
confidence: 99%
“…Cumulative corticosteroid dosage was not associated with increased fracture risk in this analysis. Finally, it has been shown that BMD at the distal radius is predictive of fracture risk and correlates with parathyroid hormone (PTH) levels in patients who have CKD 5 and are on hemodialysis (16).…”
Section: Is There An Increased Fracture Risk After a Kidney Transplant?mentioning
confidence: 99%